DNA Methylation and RNA-Sequencing Analysis Show Epigenetic Function During Grain Filling in Foxtail Millet (Setaria italica L.) - Wang, Tao; Lu, Quanwei; Song, Hui; Hu, Nan; Wei, Yangyang; Li, Pengtao; Liu, Yuling; Zhao, Zilin; Liu, Jinrong; Zhang, Baohong; Peng, Renhai (Frontiers in Plant Science, 2021)
Grain filling is a crucial process for crop yield and quality. Certain studies already gained insight into the molecular mechanism of grain filling. However, it is unclear whether epigenetic modifications are associated with grain filling in foxtail millet. Global DNA methylation and transcriptome analysis were conducted in foxtail millet spikelets during different stages to interpret the epigenetic effects of the grain filling process. The study employed the whole-genome bisulfite deep sequencing and advanced bioinformatics to sequence and identify all DNA methylation during foxtail millet grain filling; the DNA methylation-mediated gene expression profiles and their involved gene network and biological pathway were systematically studied. One context of DNA methylation, namely, CHH methylation, was accounted for the largest percentage, and it was gradually increased during grain filling. Among all developmental stages, the methylation levels were lowest at T2, followed by T4, which mainly occurred in CHG. The distribution of differentially methylated regions (DMR) was varied in the different genetic regions for three contexts. In addition, gene expression was negatively associated with DNA methylation. Evaluation of the interconnection of the DNA methylome and transcriptome identified some stage-specific differentially expressed genes associated with the DMR at different stages compared with the T1 developmental stage, indicating the potential function of epigenetics on the expression regulation of genes related to the specific pathway at different stages of grain development. The results demonstrated that the dynamic change of DNA methylation plays a crucial function in gene regulation, revealing the potential function of epigenetics in grain development in foxtail millet.